Resident and Non-resident Father Involvement, Coparenting, and the Development of Children’s Self-Regulation Among Families Facing Economic Hardship - Altenburger, Lauren E. (Frontiers in Psychology, 2022)
Self-regulation, or the ability to effectively manage emotions and behavior, is a critical skill to develop in early childhood. Children living in a context of economic hardship are at an increased risk for developing self-regulation difficulties. However, few studies have comprehensively examined how multiple aspects of the caregiving environment, including fathers’ parenting and coparenting quality, may contribute to child self-regulation. Thus, this study applied a family systems perspective to examine whether coparenting and resident and non-resident fathers’ reports of parenting quantity and quality were associated with observations of children’s self-regulation. Participants were drawn from the Embedded Developmental Study (n = 257) of the Three-City Study, a longitudinal study of children and families facing economic hardship. At Wave 1, when children were 2-4 years old, reports of parenting (i.e., quantity and quality) and coparenting (i.e., support) were obtained. At Wave 2, when children were 3-6 years old, children participated in a snack delay and gift wrap task, which assessed their self-regulation. Multi-group path analyses indicated that resident fathers’ harsh parenting at Wave 1 predicted decreased levels of self-regulation at Wave 2. Non-resident fathers’ reported hours of involvement at Wave 1 predicted greater levels of self-regulation at Wave 2. Additionally, supportive coparenting among families with a non-resident father predicted greater self-regulation. Supportive coparenting was not associated with child self-regulation in families with a resident father. The implications for research focused on facilitating positive father-child relationships in diverse family contexts are discussed.